2019
DOI: 10.1002/mds.27664
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive vagus nerve stimulation to target gait impairment in Parkinson's disease

Abstract: Gait impairments in Parkinson's disease (PD) are often present at diagnosis and respond selectively to treatment. 1 Novel interventions targeting dopa-resistant gait impairments and their consequences-falls risk-are urgently needed. Recent evidence suggests that neuronal cholinergic loss from the basal forebrain (nucleus basalis of Meynert) and brain stem (pedunculopontine nucleus) contribute to a functional decline in gait. 2 A noninvasive technique that activates the cholinergic circuitry, which has gained r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 7 publications
2
32
1
Order By: Relevance
“…51 Studies assessing the effects of cholinergic augmentation, via pharmacological intervention (i.e., rivastigmine and donepezil) or vagus nerve stimulation, have observed significant reduction of gait variability in people with PD. 52,53 Among various gait domains assessed in the current study, only gait variability (i.e., step time variability) responded to the combined intervention. Thus, it is possible to speculate that the addition of anodal tDCS over the PFC to a session of aerobic exercise may have increased cholinergic activity, leading to reduced gait variability.…”
Section: Discussionmentioning
confidence: 79%
“…51 Studies assessing the effects of cholinergic augmentation, via pharmacological intervention (i.e., rivastigmine and donepezil) or vagus nerve stimulation, have observed significant reduction of gait variability in people with PD. 52,53 Among various gait domains assessed in the current study, only gait variability (i.e., step time variability) responded to the combined intervention. Thus, it is possible to speculate that the addition of anodal tDCS over the PFC to a session of aerobic exercise may have increased cholinergic activity, leading to reduced gait variability.…”
Section: Discussionmentioning
confidence: 79%
“…Another preclinical PD study in rats demonstrated that transcutaneous auricular VNS alleviated neuroinflammation, resulting in reduced SN-DA phenotypic loss and greater motor function, possibly through nicotinic acetylcholine receptor activation [46]. Small human pilot studies in PD showed that a single session of transcutaneous VNS can improve gait [47,48], highlighting the Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…While in rodents these results happened on the order of days to weeks [5,10,66], it is important to note that in epilepsy and depression patients, VNS effects occurred over longer periods on the order of months to years [67e70]. Therefore, while initial pilot studies using external VNS suggested promising motor benefits for PD [47,48], a similar timecourse should be expected for long-term VNS treatment in PD patients due to chronic, ongoing degeneration. While other anti-inflammatory strategies such as nonsteroidal anti-inflammatory drugs have failed to yield convincing clinical results for PD [71], VNS provides greater benefit by altering multiple mechanisms of degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its clinical properties and widespread effects on Central and Autonomic Nervous Systems (CNS/ANS), VNS may be a suitable therapy in PD as highlighted below in the main body of our manuscript. The effects of nVNS on gait problems in human participants with PD has been demonstrated in three recent publications [24][25][26]. Furthermore, some recent studies have investigated the clinical efficacy of VNS for reducing symptoms that often occur in PD, including fatigue [27] and gastrointestinal symptoms [28,29], neuropsychiatric disorders [30,31], dementia [32,33] and essential tremor [34] providing further theoretical support.…”
Section: Introductionmentioning
confidence: 99%